ENVIRONMENTAL LAW IN INDONESIA: BALANCING DEVELOPMENT AND CONSERVATION - Alexander Jonathan Wijaya; Clarissa Adelia Elizabeth; Mariska Putri Hernani; Resa Panjaitan⁴ Resa Panjaitan⁴ (Problematika Hukum, 2021)
With Indonesia’s dynamic environment and economy, development, and conservation in both factors is mandatory to maintain its continuity. The environmental law's role and prospect as an agent of balance, agent of conservation, and certainly agent of change is an issue that cannot be negotiated to achieve healthy and sustainable development in Indonesia. With the main issue being emissions, Indonesia’s progress in achieving a “green” economy lingers in a pause. However, amidst these challenges, Indonesia has set its sights towards a brighter future, aimed at mitigating emissions and fostering an energy transition. Its commitment towards net-zero emission is underlined. It aims to provide a road map for bolstering Indonesia's environmental legislation, igniting revolutionary change, and cultivating a future in which development and conservation live in harmony, protecting Indonesia's natural heritage and guiding the country toward a prosperous and sustainable future in the field of the green economy and achieving the SDGs. Using an extensive examination of legal frameworks, empirical qualitative data, case studies, and stakeholder viewpoints, this study aims to illuminate the obstacles, prospects, and possible routes for Indonesia to manage the equilibrium between development and preservation within the framework of emissions mitigation.Net-Zero Emission, Environmental Law, Green Economy